Disaster Medicine in Low-Resource Settings Recent Challenges and Innovations - Agastya, Wayan Dhea (Journal of Diverse Medical Research: Medicosphere, 2024)
Background. Disaster medicine in low-resource settings faces many challenges. Most are aggravated by limited infrastructure, scarce medical supplies, and insufficiently trained health professionals. This calls for complexity in responding to these events due to enhanced logistic challenges and sociopolitical instability, according to which may hamper effective and timely medical interventions. Methods. Literature searching was conducted using databases such as PubMed, Google Scholar, and Web of Science using Search terms included "disaster medicine," "low-resource settings," "emergency response," and "innovations in disaster care.". Systematic reviews of peer-reviewed articles, reports, and case studies were chosen.